2015
DOI: 10.2217/fmb.14.123
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Pertussis Toxin and its Impact on Vaccination

Abstract: Whooping cough, caused by Bordetella pertussis, remains a major global health problem. Each year around 40 million of pertussis cases resulting in 200,000-400,000 annual deaths occur worldwide. Pertussis toxin is a major virulence factor of B. pertussis. Murine studies have shown its importance in bacterial colonization and in immunomodulation to evade innate or adaptive immunity. The toxin is composed of an A protomer expressing ADP-ribosyltransferase activity and a B oligomer, responsible for toxin binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 117 publications
0
14
0
1
Order By: Relevance
“…Those authors also found that lethality was reduced upon infection by B. pertussis strains with undefined transposon insertions putatively reducing secretion of pertussis toxin (PT) (15,16). PT, a secreted virulence factor of B. pertussis (17), ADP-ribosylates G ␣i proteins in mammalian cells, disrupting G protein-coupled receptor (GPCR) signaling (18,19). In adult mice, PT plays an important early role in promoting infection by inhibiting innate immune responses (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Those authors also found that lethality was reduced upon infection by B. pertussis strains with undefined transposon insertions putatively reducing secretion of pertussis toxin (PT) (15,16). PT, a secreted virulence factor of B. pertussis (17), ADP-ribosylates G ␣i proteins in mammalian cells, disrupting G protein-coupled receptor (GPCR) signaling (18,19). In adult mice, PT plays an important early role in promoting infection by inhibiting innate immune responses (20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Pertussis toxin (PTX) in an inactivated form (PTd) functions as a major protective antigen, stimulating production of toxinneutralizing antibodies which can protect against damage caused by the toxin, but do not target the bacteria itself (301,302); however, it also demonstrates possible partial reversion back to its toxic active form (303,304), which may be responsible for the reactogenicity seen in a small percentage of vaccine recipients. It is also a secretory protein, which is only loosely associated with the cell and is therefore not an ideal target for bactericidal antibodies.…”
Section: Los-derived Oligosaccharide Glycoconjugatesmentioning
confidence: 99%
“…Since the move to aPV in most countries in recent years, a detoxified form of PT has been a component of all of these vaccines, in recognition of its role as a protective antigen against severe disease in infants (Coutte and Locht 2015). Although most of these vaccines contain other pertussis antigens, a monocomponent detoxified PT vaccine is used in Denmark (Thierry-Carstensen et al 2013).…”
Section: Pt As a Pertussis Vaccine Component And Therapeutic Targetmentioning
confidence: 99%